UJI AKTIVITAS PERTUMBUHAN RAMBUT KOMBINASI EKSTRAK ETANOL DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) DAN DAUN LIDAH MERTUA (Sansevieria trifasciata Prain.) - Gina Septiani Agustien (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2018)
ABSTRACT The frequency and quantity of hair loss problems increases which eventually leads to baldness. The use of medicinal plants today is very popular and increasingly favored by the community. Plants are efficacious as a hair grower such as pandanus leaves (Pandanus amaryllifolius Roxb.) and sansevieria leaves (Sansevieria trifasciata Prain.). The purpose of this study to determine the hair growth activity of a combination of pandanus leaves extract and sansevieria leaves. Test preparation was made by combining both extracts at 5% concentration with comparison of pandanus leaves extract and sansevieria leaves 1: 1, 2: 3 and 3: 2. The results showed that the combination of 3: 2 has the best hair growth activity. Testing of this hair growth activity is a combination extract compared to normal control, 96% ethanol and minoxidil. The result of hair growth activity showed that the combination extract had better activity than the sole extract. Key word : hair growth activity, pandanus leaves, sansevieria leaves, extract combination.